Lidocaine 2% and Xylocaine Spray as A Combination in Successful Awake Intubation in Difficult Airway: How to Do it? - Murti, Dede Taruna Kreisnna; Senapathi, Tjokorda Gde Agung; Pradhana, Adinda Putra; Labobar, Otniel Adrians (Syntax Literate, 2025)
Awake intubation is a technique used to insert an endotracheal tube while maintaining the patient's consciousness. It is particularly beneficial for patients with difficult airway anatomy, as it allows better visualization using a fiber optic bronchoscope, reduces discomfort with local anesthesia, and ensures the preservation of spontaneous breathing. This approach is critical in high-risk procedures such as total thyroidectomy. This case report aims to describe the application of awake intubation in a high-risk patient undergoing total thyroidectomy due to a thyroid mass causing tracheal narrowing. A 47-year-old female with airway management difficulties (LEMON 3/10, MOANS 0/5) was scheduled for a 3–4-hour total thyroidectomy. Preoperative preparation included fasting, informed consent, and ensuring complete anesthesia equipment. Airway preparation involved Xylocaine spray and Lidocaine nebulization, followed by premedication with Dexamethasone, Diphenhydramine, and Midazolam. Induction was achieved using Propofol, and intubation was performed with an endotracheal tube guided by a fiber optic bronchoscope. Maintenance of anesthesia utilized Oxygen, Sevoflurane, and Atracurium. The results show the patient tolerated the awake intubation procedure well, with no episodes of desaturation or significant bleeding during surgery. Postoperative management included analgesia with Fentanyl and Ketamine, as well as respiratory therapy intervention (RTI) during recovery. Awake intubation, combined with effective airway preparation and anesthesia protocols, provides a safe and reliable approach for managing patients with difficult airways, particularly in high-risk procedures like total thyroidectomy. The technique ensured patient comfort, maintained oxygenation, and minimized perioperative complications.